Influence of Winter Storms on the Sea Urchin Pathogen Assemblages - Salazar-Forero, Camila Esperanza; Reyes-Batlle, María; González-Delgado, Sara; Lorenzo-Morales, Jacob; Hernández, José Carlos (Frontiers in Marine Science, 2022)
In recent years, recurrent sea urchin mass mortalities in the Canary Islands have been registered. These mortality-related events have decimated 93 % of the eastern Atlantic populations of the barren-forming sea urchin Diadema africanum. Two severe episodes of rough southeastern seas led to winter storms in February 2010 (Xynthia) and February 2018 (Emma) and preceded the last mass mortality event. We hypothesized that these events are related to the mass mortalities registered during the February in those years. Previous studies identified Neoparamoeba branchiphila as the causal agent of the disease, possibly acting in synergy with Vibrio alginolyticus and/or other pathogens. To determine the link between winter storms and the sea urchin pathogen community, we monitored the marine pathogen assemblage before and after the winter storm Filomena (February 2020) on Tenerife Island, on different habitats (sea water, sediment and algae) and in four species of sea urchin hosts (D. africanum, Arbacia lixula, Paracentrotus lividus and Sphaerechinus granularis). A total of six pathogens, including N. branchiphila, Vexillifera minutissima, Acanthamoeba sp., Vahlkampfia sp., V. alginolyticus and green colonies of Vibrio spp., were identified. Only small amoebas were found in sea urchins, while Vibrio species were more common in seawater, sediment and algae substrates. V. alginolyticus was occasionally detected in three sea urchins specimens, while N. branchiphila was found in the coelom of all four sea urchin studied. As previously hypothesized, a significant pathogen increment in seawater and in the sea urchin species D. africanum and P. lividus, was found after Filomena. Our results confirmed the relationship between the winter storms and marine pathogen dynamics. However, further studies are needed to demonstrate the direct relationship between these pathogen increases and the sea urchin mass mortalities.